Bubble dynamics in soft materials: Viscoelastic and thermal effects. (November 2015) - Johnsen, Eric; Mancia, Lauren
Abstract: The oscillations of a single spherical bubble in a soft surrounding medium are investigated numerically. In particular, the combined effects of the viscoelasticity and compressibility of the surroundings, as well as subsequent heating, on the bubble dynamics are quantified for forced and free collapse. In a Keller-Miksis framework, a Kelvin-Voigt viscoelastic model with full thermal effects is considered, in which the elastic term is represented by a Neo-Hookean model to account for the finite strains. The history and spatial distribution of the stresses and temperatures produced in the surroundings are examined and related to potential cavitation damage mechanisms.